(untitled) (International Current Pharmaceutical Journal, 2017)
In this present study, 1500 Diabetes Mellitus (DM) patients were included from Coimbatore zone, Tamil Nadu, India. The blood glucose levels were monitored to correlate the glycemic control with the antidiabetic drug treatment. This study addressed many variabilities in such treatments including the prescribing pattern of various novel entities along with existing drugs for glycemic control, diabetic vascular complexities on Coimbatore zone, lack of relevant scientific data, occurrences of prescription errors, less awareness of the DM patients, the insufficient number of local hospitals and high cost of the medicine. Data analysis was carried out by segregating the DM patients under study according to their blood glucose level. Results demonstrated that brand names of anti-diabetic drugs were taken more frequently by outpatients when contrasted with inpatients. Also, the number of drugs prescribed under generic names were significantly less than prescribe brand names. Prescribed formulations results indicated that tablets were preferred over other formulations. Frequently prescribed twenty-one brands and their combination results demonstrated the popularity of the insulin human Mixtard® injection 30-40 IU. Moreover, frequently prescribed 21 branded drugs’ cost were analyzed. It can be concluded from the current work that appropriate steps should be taken to raise awareness of the DM patients in Coimbatore zone so that they can follow the specialists’ instruction for better hyperglycemia control. Finally, it can be suggested that the Tamil Nadu Government should put more effort on improving health care support in Coimbatore zone. Govindasamy and Sellappan, International Current Pharmaceutical Journal, April 2017, 6(5): 27-33 http://www.icpjonline.com/documents/Vol6Issue5/01.pdf